The Effect of Tax Planning, Deferred Tax Expense, Leverage, and Financial Distress on Earnings Management in Manufacturing Companies in the Consumer Goods Industry Sector Listed on the IDX in 2014-2018: Pengaruh Tax Planning, Beban Pajak Tangguhan, Leverage, Dan Financial Distress Terhadap Manajemen Laba Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di BEI Tahun 2014-2018 - Andayani, Fatma Dwi; Setiyono, Wisnu Panggah (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to examine the effect of tax planning, deferred tax burden, leverage, and financial distress on earnings management. The approach used in this study is a quantitative approach with a sampling technique using purposive sampling method. The sample in the study was 10 manufacturing companies in the consumer goods industry sector listed on the IDX in 2014-2018. The analytical technique used in this study is panel data regression analysis with the help of the Eviews9 program. The results of this study indicate that the tax planning variable has no effect on earnings management, deferred tax expense has a negative effect on earnings management, leverage has a positive effect on earnings management, financial distress has no effect on earnings management and simultaneously tax planning, deferred tax expense, leverage, financial distress has no effect on management.